TECHNIKI OBRAZOWANIACoronary artery calcium evaluation by computed tomography. Relation to severity of coronary artery atherosclerosis and cardiovascular risk - Wasilewski, Jarosław; Miszalski-Jamka, Karol; Hudzik, Bartosz; Głowacki, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Coronary arterial calcification is part of the development of atherosclerosis, occurs almost exclusively in atherosclerotic arteries, and is absent in the normal vessel wall. Although there is a positive correlation between the site and the amount of coronary artery calcium and the percent of coronary luminal narrowing at the same anatomic site, the relation is nonlinear. The paper rewiev the prognostic value of coronary calcium clacification and its relation with severity of coronary artery atherosclerosis.